PRZESTĘPSTWO TZW. OSZUSTWA UBEZPIECZENIOWEGO (ART. 298 KODEKSU KARNEGO) - UWAGI ZASADNICZE - Pohl, Łukasz (Wydział Prawa i Administracji UAM, 2001)
At the outset of the article the Author critically discusses terminological issues related to the Article 298 of the Penal Code. The offence of staging an accident in order to obtain an indemnity has been included in chapter XXXVI Penal Code, which means that it has been classified as an offence against economic relations. The proper object of protection is in this case the security of economic relations, while the direct object of protection is the convenience of insurers and the closely related and mutually conditioning interests of both insurers and the insured parties. Later on in the article the Author focuses upon the offence subject and the features determining the enforcement proceedings. Finally, he deals with the subject since he considers that an offence specified in Art. 298 of the Penal Code is an oriented offence, which means that it is determined by a specific aim (obtaining the indemnity). The Author also discusses the institution of the so-called active repentance, according to which a person is not liable to a penalty if he voluntarily prevents the payment of indemnity before the beginning of the proceedings.
INSURANCE FRAUD (ART. 298 POLISH PENAL CODE)